Mosby's physical examination DVD series : DVD 13, Musculoskeletal system [ - Ball, Jane; Benedict, G. William; Dains, Joyce E.; Seidel, Henry M. (Mosby's physical examination DVD series, 2006)
"This 23 minute video shows the steps needed to examine the musculoskeletal system, including the proper use of equipment. With the patient standing, it demonstrates how to assess gait, posture, and alignment. With the patient in various positions, it shows how to inspect and palpate the muscles, joints, and bones and how to percuss the spine. It also presents muscle-strength and range-of-motion testing, identifying the expected degrees of movement. The video highlights expected findings and alerts the viewer to selected variations in pediatric and geriatric patients."--Publisher's website